The Implementation Of Multicultural Education, Democratic Education, And Human Rights Education In Educational Practice: A Case Study At Mts Hidayatul Falah Nagrak, Sukabumi Regency - Tamlekha, Tamlekha; Hariyanto, Teguh; Napisah, Nina; Kosim, Rijal Muhamad; Erihadiana, Mohamad (UNIVERSITAS PAKUAN, 2025)
This study aims to describe the implementation of multicultural, democratic, and human rights (HR) education values at MTs Hidayatul Falah Sukabumi. The research employed a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and document analysis. The findings indicate that the school has made efforts to realize inclusive, participatory, and equitable education through various learning activities and internal policies. However, the implementation still faces challenges such as limited teacher training and a socially homogeneous environment. This study recommends strengthening policy frameworks and teacher training programs to achieve a more systematic and comprehensive value-based education.